Seasonality patterns of the Chinese outbound travelers: Evidence from eight leading tourist destinations in Asia - Rabeeu Ahmed; Ramos Disney Leite (Bahasa Indonesia, 2023)
The Chinese outbound market has surpassed that of any country in the world in recent years. It specifically became the leading source market for many Asian countries. In this respect, this study uses a monthly dataset of tourist arrivals from 1995 to 2019 to investigate the seasonality patterns of Chinese outbound tourists in eight tourist destinations in Asia popular among Chinese tourists. The Gini coefficient and the Seasonal Index were used to examine the seasonality patterns. The results of this research reveal a generally consistent pattern across all destinations examined, confirming the occurrence of two distinct peaks (i.e., February and July to August) and off-peak (i.e., March to June and November to December) periods. The findings further show the expansion of the Chinese market has considerably softened the seasonality in the inbound tourism of the countries studied. Finally, key implications of the study findings are discussed, highlighting some practical insights that might help practitioners manage seasonality.